2017
DOI: 10.1038/ncomms15488
|View full text |Cite
|
Sign up to set email alerts
|

Mir-132/212 is required for maturation of binocular matching of orientation preference and depth perception

Abstract: MicroRNAs (miRNAs) are known to mediate post-transcriptional gene regulation, but their role in postnatal brain development is still poorly explored. We show that the expression of many miRNAs is dramatically regulated during functional maturation of the mouse visual cortex with miR-132/212 family being one of the top upregulated miRNAs. Age-downregulated transcripts are significantly enriched in miR-132/miR-212 putative targets and in genes upregulated in miR-132/212 null mice. At a functional level, miR-132/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 71 publications
(129 reference statements)
2
32
0
Order By: Relevance
“…To evaluate the role of Rbfox1 on visual function, the visual cliff test was used. The test evaluates the functional integrity of the retino-geniculo-cortical pathway by determining the depth perception of the animal [ 27 , 34 ]. The test is based on the animals’ innate tendency to avoid the deep side of the chamber.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the role of Rbfox1 on visual function, the visual cliff test was used. The test evaluates the functional integrity of the retino-geniculo-cortical pathway by determining the depth perception of the animal [ 27 , 34 ]. The test is based on the animals’ innate tendency to avoid the deep side of the chamber.…”
Section: Discussionmentioning
confidence: 99%
“…Test was performed as previously described 76,77 with modifications. A transparent Plexiglas square arena (30 × 30 cm) was divided into two equal parts by aligning the middle of the arena with the edge of the table.…”
Section: Methodsmentioning
confidence: 99%
“…Because previous studies suggested that miR-132 made an important contribution to neuronal function and maturation, 14 , 15 , 21 , 25 we conducted therapeutic trials to see what would happen to HD mice if miR-132 were supplied to the HD brains. To compensate for the shortage of miR-132 in HD brains, we constructed a viral miR-132- expression system using recombinant adeno-associated viruses (rAAVs).…”
Section: Resultsmentioning
confidence: 99%